Relationships of Black-Fly Species of the Simulium tuberosum Species-Group (Diptera: Simuliidae) in Peninsular Malaysia, with Keys to Ten Malaysian Species - Takaoka, H.; Sofian-Azirun, Mohd; Hashim, R.; Otsuka, Y.; Belabut, D.M.; Ean, T.P. (National University of Singapore, 2012)
Two species of black flies, Simulium (Simulium) jasmoni Takaoka, Sofian-Azirun & Belabut, 2012 and S. (S.) tiomanense Takaoka, Sofian-Azirun & Belabut, 2012, described from Tioman Island, Pahang, Malaysia, are placed in two different lineages of the tuberosum species-group in the subgenus Simulium (Simulium) Latreille, and have close similarities to S. (S.) tani Takaoka & Davies, 1995 and S. (S.) brevipar Takaoka & Davies, 1995, respectively, which were the only members of the same species-group in the nearest mainland of Peninsular Malaysia. It is suggested that S. (S.) jasmoni and S. (S.) tani in one lineage, as well as S. (S.) tiomanense and S. (S.) brevipar in another, had a common vicariant origin and were isolated after sea levels rose. Comparisons of character states of several pupal morphological features among four species in one lineage and five species in another lineage show that both S. (S.) jasmoni and S. (S.) tiomanense on Tioman Island retain more putative ancestral characters than S. (S.) tani and S. (S.) brevipar and other species in the same lineages on the continent and its adjacent large islands. Keys to 10 Malaysian members of the tuberosum species-group are provided for females, males, pupae, and mature larvae. Â© National University of Singapore.